Factors Associated with Perceived Insufficient Milk in the First Three Months of Breastfeeding. Issue 4 (July 2021) - Wood, Natsuko K.; Odom-Maryon, Tamara; Smart, Denise A.
Abstract: Purpose: Perceived insufficient milk is the predominant risk factor for early breastfeeding discontinuation globally. The purpose of this study was to explore the association between perceived insufficient milk in the first 3 months and infant factors, maternal factors, professional support, parenting decisions, and breastfeeding concerns. Sixty-nine mothers who had perceived insufficient milk and 301 mothers who did not were included. Study Design and Methods: A cross-sectional online survey design was used in a convenience sample of 370 U.S. mothers with a healthy singleton infant between 1 and 12 weeks who were breastfeeding directly on the breast as part of their feeding methods. Results: Using stratified multivariable logistic regression, we found that among 102 mothers of infants < 4 weeks of age, planned breastfeeding duration < 6 months (OR = 13.17; 95% CI [1.42, 122.48], p = .024), and concerns about infant crying or fussing (OR = 4.72; 95% CI [1.10, 20.00], p = .03) were associated with perceived insufficient milk. Among 256 mothers of infants 4 to 12 weeks of age, concerns about frequent feedings (OR = 4.05; 95% CI [1.95, 8.40], p = .000) and latching difficulty (OR = 2.95; 95% CI [1.33, 6.54], p = .008) were associated with perceived insufficient milk. Clinical Implications: Association between factors and perceived insufficient milk differed based on infant age. Maternal perceptions of crying or fussing, frequent feedings, and latching difficulty need to be assessed because of its attribution to perceived insufficient milk. Abstract : Some women who are breastfeeding stop before they had planned when they perceive they have an insufficient supply of breast milk. In this study, maternal perceptions of crying and fussing, frequent feedings, and latching difficulty were identified as factors breastfeeding mothers attributed to perceived insufficient milk. Nurses can assess for these factors and offer reassurance that they are generally normal and not a sign of insufficient breast milk supply, so new mothers do not unnecessarily cease breastfeeding earlier than they planned.